Public policy for democracy / edited by Helen Ingram and Steven Rathgeb Smith - "Smith, Steven Rathgeb.(ed.)" (Hyderabad, 1995)
This work is a testimony to the ability of an ideal public policy designed to foster democracy to galvanize a collective effort to over come barriers of different disciplines, ideologies, institutions, and geographic locations.
Keywords: Political participation United states